Rapid bacteriophage quantification with a particle size analyzer combined with polarization intensity differential scattering (PIDS) detector - Amanda Carroll-Portillo; Cody A Braun; Edgar Martinez; Henry C Lin (PLoS ONE, 2026)
The study of bacteriophages (phages) and effects on their microenvironments expanded exponentially within the last decade. While there are multiple described methods for phage quantitation, there is still a need for a rapid, label-free method. To this end, we established a procedure for rapid phage quantitation through novel use of a particle size analyzer with Polarization Intensity Differential (PIDS) technology and eliminated the need for labels or knowledge of bacterial host. We validated the procedure and analysis method, termed PhageFOTO (Fast Optical Tallying of Objects) using several physiologically different phages ranging from ~6 nm capsid width ( Inoviridae ) to ~90 nm capsid width ( Caudoviricetes ). PhageFOTO demonstrated 89 ± 4.3%, 98 ± 1.7%, and 94 ± 2.7% accuracy for quantitating PhiX, M13, and T4 phages/mL respectively as compared to the gold standard plaque assay with limit of detection for particle concentration occurring around 10 7 phages/mL. PhageFOTO proved to be a novel, rapid, label free method for phage counting that does not rely on knowledge of the bacterial host presenting unique capability for quantitation of phage samples.